Homonymous Retinal Ganglion Cell Layer Atrophy With Asymptomatic Optic Tract Glioma in Neurofibromatosis Type I - Momen, Amirah I.; Muir, Ryan T.; Barnett, Carolina; Sundaram, Arun N. E. (Frontiers in Neurology, 2020)
Approximately twenty percent of patients with Neurofibromatosis type 1 (NF1) develop optic pathway gliomas (OPGs). Not all OPGs in NF1 necessarily become vision compromising and predicting which patients might develop visual decline is difficult at present time. Optical coherence tomography (OCT) has emerged as a useful tool able to directly assess the morphology and thickness of individual retinal layers. The ganglion cell layer (GCL) is composed of the retinal ganglion cells which receive information from photoreceptors via interneurons, while the retinal nerve fiber layer (RNFL) contains the retinal ganglion cell unmyelinated axons that merge to form the optic nerve. Lesions of the anterior visual pathway result in retrograde axonal degeneration from ganglion cell death and ultimately manifest as thinning of the RNFL and/or GCL. In this report we highlight a case of a 38 year-old woman with an NF1 associated left chiasmal and optic tract glioma who had normal visual fields and visual acuity. However, using OCT we demonstrate a homonymous pattern of GCL atrophy that corresponds with her left optic tract glioma. Given this homonymous pattern of atrophy in the GCL and the left optic tract lesion, one would expect a right homonymous hemianopia. To our knowledge this is the first reported case of a homonymous pattern of GCL-IPL atrophy in an adult with an NF1 related OPG involving the optic chiasm and optic tract, but without objective visual field or acuity deficits. This case is important because, mechanistically, it suggests that a necessary threshold of GCL atrophy may be needed before visual concerns can be detected and, secondly, it invites future studies to evaluate whether OCT may serve as a potential screening tool for those with NF1 related OPGs.